SOME PROPERTIES OF GENERALIZED EIGENFUNCTIONS OF ONE CLASS OF DIFFERENTIAL OPERATORS - Asatryan, H.A.; Sargsyan, T.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
In the paper considers continuality in a parameter of generalized eigenfunc-tions of one class of differential operators. Properties of one class of functions constructed by means of the generalized eigenfunctions and used in the theory of integral equations are studied.
Keywords: differential operator; generalized eigenfunction; spectral decompo-sition; integral equation